Perbedaan Lama Pelepasan Tali Pusat Berdasarkan Perawatan Tali Pusat Pada Bayi Baru Lahir - Hariyanto Hariyanto; eva febriana (Akbid Harapan Mulya Ponorogo, 2018)
This study aimed at determining the difference in the length of umbilical cord release based on umbilical cord care. This research was conducted from February to April 2017. This type of research was an experimental research and the design used was cross sectional. The population in this study were 42 pregnant women estimated to give birth in February-April 2017. The sample of the research was 30 newborns taken with porposive sampling technique. Data collected by observation. Data were analyzed using T Test statistic test result. The results showed that most, 19 respondents (63,3%) had performed the umbilical cord care technique correctly. Almost half of respondents, 13 respondents (43,3%) the umbilical cord was release fast. The significant level was 0,000 < 0,50, so it was concluded that there was a difference in the length of umbilical cord removal based on umbilical cord care techniques. If the umbilical cord care is correct, it was removed or healed quickly. Based on the results of the study is expected health workers, especially midwives are encouraged to continue using the correct care of the umbilical cord or sterile gauze because it only covers the umbilical cord with sterile gauze, the cord will dry faster and the cord will release quickly.